Kajian efek interaksi antihipertensi dengan obat antiinflamasi nonsteroid (OAINS) terhadap tekanan darah pada pasien hipertensi - Ayubi, Ihsan Shabirin Al; Faizah, Ana Khusnul; Yusan, Liza Yudhistira (Sasambo Journal of Pharmacy, 2024)
Hypertension causes atherosclerosis which can cause occlusion resulting in subchondral ischemia, which causes the exchange of nutrients and gases into the articular cartilage, which is disrupted and becomes the potential initiator of degradative changes or the so-called osteoarthritis. This review aims to evaluate the effect of antihypertensive drug interactions with NSAIDs on blood pressure. This article review was conducted using a narrative review study. The inclusion criteria in this article are the pharmacodynamic interaction of antihypertensives with NSAIDs in hypertensive patients with osteoarthritis. The results obtained seven articles that meet the inclusion criteria. Hypertensive patients with osteoarthritis receive medications that must be monitored because a drug-drug interaction can decrease the effectiveness of antihypertensives. One of the most widely used drugs in antihypertensive therapy is ACEi, but NSAIDs inhibit the antihypertensive effect on prostaglandin synthesis resulting from bradykinin production. The decrease in blood pressure stimulated by bradykinin plays an essential role in vasodilatation. The interaction of ACEi and NSAIDs can cause an increase in blood pressure with a minimum expansion of 1.1 mmHg. Still, when administering NSAIDs with CCBs, a decrease in blood pressure of 2.86 mmHg is obtained because the action is not dependent on prostaglandins. Based on the results, there were pharmacodynamic changes for both antihypertensive drugs and NSAIDs due to drug interactions that affected the patient's clinical outcome in the form of blood pressure.